Analisis Kesalahan Struktur Pada Tulisan Jawaban UlanganTengah Semester Siswa Kelas Xi Ips Di Sma Muhammadiyah 2Surakarta - Apriyanto, Aris, Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
The study, entitled analysis of structure errors in writing answers to class XI IPS in SMA Muhammadiyah 2 Surakarta has a purpose (1) Describe the structure of form errors on writing midterm quiz answers class XI student at SMA Muhammadiyah 2 Surakarta. (2) Find and explain mistakes dominant structure in writing midterm quiz answers class XI student at SMA Muhammadiyah 2 Surakarta. This study is a qualitative research, this study was conducted by taking data from school SMA Muhammadiyah 2 Surakarta. The data used by researchers is written midterm quiz answers class XI IPS. Data collection techniques used in this study using the technique see and record, meant to hold menyimakan and recording of relevant data, in accordance with the goals and objectives of the study. Data were analyzed using a unified method intralingual. Padan is a word that is synonymous with the word appeal and meaning something than what their connectedness that frontier is a matter that contains a comparison while intralingual refers to the meaning of the elements that are in the language. The results of this study include five things: 1) error structure because of the ambiguity of activepassive, 2) Errors structure for the subject and information, 3) Error structure for the introductory sentence, 4) Errors structure for connecting divided less precise, 5) Mistakes structure in the absence of main clause. Keywords: case, pattern, structure errors